ANALISIS POPULASI NEPENTHES SPP DI HUTAN RAWA GAMBUT, KALAMPANGAN, KALIMANTAN TENGAH - Muhammad Mansur (Center for Environmental Technology - Agency for Assessment and Application of Technology, 2010)
Population analysis of Nepenthes spp in peat swamp forest was conducted atKalampangan, Central Kalimantan on November-December 2007. This place include to part of one million hectare area of peat land project in 1996 which are planed to convert agricultural land. Peat swamp forest is one of commonly Nepenthes habitat at Kalampangan. One plot (50 x 100 m) was establihed for population analysis study. We found 230 individu from three species, that is; Nepenthes ampullaria, N. rafflesiana and N. gracilis. In study site, N. ampullaria is dominant species with Important Value (IV) is 120,43% and then followed by N. gracilis (IV= 97,30%) and N. rafflesiana (IV= 82,27%).Key Words : Population analysis, Nepenthes, peat swamp forest, Kalampangan,